2020
DOI: 10.47102/annals-acadmedsg.2020106
|View full text |Cite
|
Sign up to set email alerts
|

Chest Radiography in Coronavirus Disease 2019 (COVID-19): Correlation with Clinical Course

Abstract: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 and was declared a global pandemic by the World Health Organization on 11 March 2020. A definitive diagnosis of COVID-19 is made after a positive result is obtained on reverse transcription-polymerase chain reaction assay. In Singapore, rigorous contact tracing was practised to contain the spread of the virus. Nasal swabs and chest radiographs (CXR) were also taken from individuals who were suspected to be infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another case series from Singapore published by Zhou et al confirmed that around 40% of patients with COVID-19 PCR positive had initial normal CXR; however, these patients were stable and most of them did not require admission to hospital. One of their patients had initial normal CXR, but as the patient deteriorated and required 35% of oxygen, the repeat CXR started to show features of classic COVID-19 in the form of unilateral consolidation that later on progressed later to bilateral consolidation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another case series from Singapore published by Zhou et al confirmed that around 40% of patients with COVID-19 PCR positive had initial normal CXR; however, these patients were stable and most of them did not require admission to hospital. One of their patients had initial normal CXR, but as the patient deteriorated and required 35% of oxygen, the repeat CXR started to show features of classic COVID-19 in the form of unilateral consolidation that later on progressed later to bilateral consolidation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of articles in this category were case reports and those about the symptoms, signs, and complications of COVID-19 . These articles described the various ways in which COVID-19 could present, such as olfactory loss [206,209,214,219], radiological findings [217,221,231,232], and various other presentations. Viral transmission of COVID-19 was the next most commonly studied [93,[243][244][245][246][247][248][249][250][251][252][253][254][255], which looked at the various modes of transmission [245,247,249,[252][253][254], and contamination of the environment and PPE [243,244,248].…”
Section: Covid-19 Pathology (94 Articles)mentioning
confidence: 99%
“…The author searched PubMed for literature reports on COVID-19 from January 20 th , 2020 to the present day. There are many reports at least 300 articles on the non-contrast enhanced high-resolution computed tomography (HRCT) features of the lungs during the onset of COVID-19; however, few studies have described the radiological changes and outcome of residual lesions in the lungs of recovered patients 3,4 .Here, we review the HRCT features of 118 recovered COVID-19 patients at 22−465 days post-discharge. These features can be utilized to predict the prognosis and guide rehabilitation treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%